(untitled) (Web of Teachers: Inderscience Research, 2025)
The results of an immunological analysis for chlamydia in pregnant women who suffered a miscarriage and had an abortion were found to be optically significant. A pathoanatomic examination of the internal organs of pregnant women who had an abortion at the age of 135-142 days showed that there were no histological data.